Autonomic nervous dysfunction in hamsters infected with West Nile virus. - Hong Wang; Venkatraman Siddharthan; Jeffery O Hall; John D Morrey (PLoS ONE)
Clinical studies and case reports clearly document that West Nile virus (WNV) can cause respiratory and gastrointestinal (GI) complications. Other functions controlled by the autonomic nervous system may also be directly affected by WNV, such as bladder and cardiac functions. To investigate how WNV can cause autonomic dysfunctions, we focused on the cardiac and GI dysfunctions of rodents infected with WNV. Infected hamsters had distension of the stomach and intestines at day 9 after viral challenge. GI motility was detected by a dye retention assay; phenol red dye was retained more in the stomachs of infected hamsters as compared to sham-infected hamsters. The amplitudes of electromygraphs (EMGs) of intestinal muscles were significantly reduced. Myenteric neurons that innervate the intestines, in addition to neurons in the brain stem, were identified to be infected with WNV. These data suggest that infected neurons controlling autonomic function were the cause of GI dysfunction in WNV-infected hamsters. Using radiotelemetry to record electrocardiograms and to measure heart rate variability (HRV), a well-accepted readout for autonomic function, we determined that HRV and autonomic function were suppressed in WNV-infected hamsters. Cardiac histopathology was observed at day 9 only in the right atrium, which was coincident with WNV staining. A subset of WNV infected cells was identified among cells with hyperpolarization-activated cyclic nucleotide-gated potassium channel 4 (HCN4) as a marker for cells in the sinoatrial (SA) and atrioventricular (AV) nodes. The unique contribution of this study is the discovery that WNV infection of hamsters can lead to autonomic dysfunction as determined by reduced HRV and reduced EMG amplitudes of the GI tract. These data may model autonomic dysfunction of the human West Nile neurological disease.